Report on the 64th Annual Scientific Congress of Japanese Society of Radiological Technology - Kamiya, Naoki; Susumu, Tachinaga; Fujita, Naotoshi; Magome, Taiki; Gotanda, Tatsuhiro (Japanese Journal of Radiological Technology, 2008)
(Article in Japanese)